2011
DOI: 10.1074/jbc.m110.188086
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of EGFR-Vav2 Signaling Axis by Cbl Ubiquitin Ligase Controls EGF Receptor-mediated Epithelial Cell Adherens Junction Dynamics and Cell Migration

Abstract: The E3 ubiquitin ligase Casitas B lymphoma protein (Cbl) controls the ubiquitin-dependent degradation of EGF receptor (EGFR), but its role in regulating downstream signaling elements with which it associates and its impact on biological outcomes of EGFR signaling are less clear. Here, we demonstrate that stimulation of EGFR on human mammary epithelial cells disrupts adherens junctions (AJs) through Vav2 and Rac1/Cdc42 activation. In EGF-stimulated cells, Cbl regulates the levels of phosphorylated Vav2 thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 80 publications
3
42
0
1
Order By: Relevance
“…8B-D) supports a model in which the hyperactivity of AKT and other upstream signaling pathways increases mTOR signaling to deplete MaSCs by promoting their rapid differentiation. Among the upstream pathways that might add to increased mTOR activity, ERK is a likely candidate as it is hyperphosphorylated when Cbl and Cbl-b are genetically deleted in HSCs or depleted by shRNA in human MECs (Duan et al, 2011). Culture of human mammary organoids with amphiregulin has been found to maintain MECs in a less differentiated state, whereas growth in EGF led to myoepithelial differentiation; this dichotomy was shown to be related to sustained ERK/RSK signaling by EGF (Pasic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…8B-D) supports a model in which the hyperactivity of AKT and other upstream signaling pathways increases mTOR signaling to deplete MaSCs by promoting their rapid differentiation. Among the upstream pathways that might add to increased mTOR activity, ERK is a likely candidate as it is hyperphosphorylated when Cbl and Cbl-b are genetically deleted in HSCs or depleted by shRNA in human MECs (Duan et al, 2011). Culture of human mammary organoids with amphiregulin has been found to maintain MECs in a less differentiated state, whereas growth in EGF led to myoepithelial differentiation; this dichotomy was shown to be related to sustained ERK/RSK signaling by EGF (Pasic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that Cbl-b exhibits a crucial function as a ubiquitin ligase and multifunctional adaptor molecule (9). A previous study demonstrated that Cbl-b is involved in the regulation of the cell cytoskeleton and adhesion (10). Furthermore, it has been reported that Cbl-b reduces cell adhesion via negative regulation of integrin and receptor-mediated signaling (11).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of cell culture experiments have suggested a role for the Vav proteins in cell migration downstream of growth factor signalling. Thus, the ubiquitously expressed mammalian Vav2 is tyrosine phosphorylated in response to different growth factors, including epidermal (EGF) and plateletderived (PDGF) growth factors, and its phosphorylation correlates with enhanced Rac activity and migration in some cell types (Duan et al, 2011;Garrett et al, 2007;Liu and Burridge, 2000;Moores et al, 2000). However, the biological relevance for many of these interactions and the cellular mechanisms by which Vav regulates in vivo cell migration remains to be determined.…”
Section: Introductionmentioning
confidence: 99%